Text and Context: Form and Meaning in Native Narratives - Chester, Blanca (Ethnologies, 1991)
Stories recorded and transcribed by Wickwire, with Robinson, an Okanagan storyteller narrating them, are compared with stories collected by Teit nearly a century earlier. Aspects of their contexts are compared and their effects on meaning examined in three ways : the context of structural interprétations; the context of discourse; and context as cultural gestalt. The définition of context is expanded to include cultural and linguistic factors which exist outside the narratives themselves, and some of the advantages of treating oral narratives as poetry are pointed out.